2019
DOI: 10.1002/adom.201901516
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Stability of Halide Perovskite CsPbX3 Nanocrystals by a Facile TPU Encapsulation

Abstract: Improving the stability of all‐inorganic halide perovskite nanocrystals has become an urgent task that cannot be ignored in practical applications. Lead halide perovskite CsPbX3 (X = Br, I, Cl) compounds are considered as the potential materials for next‐generation light‐emitting devices due to their superior optical properties. However, they are threatened by thermal degradation and atmospheric moisture. In order to better solve this practical problem, CsPbBr3 quantum dots (QDs) and CsPbBr3@Cs4PbBr6 nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 68 publications
0
37
1
Order By: Relevance
“…In addition to the enhanced optical properties, the durability of CsPbBr 3 NCs was significantly improved by the introduction of Cs 4 PbBr 6 , one such feature being their thermal stability. [189][190][191][192] In a heating and cooling cycle, the PL intensity of pristine CsPbBr 3 and CsPbBr 3 /Cs 4 PbBr 6 composite was quenched as the temperature increased. During the cooling procedure, the quenching was gradually recovered, but never recovers to the original state.…”
Section: Nanosized Compositementioning
confidence: 99%
“…In addition to the enhanced optical properties, the durability of CsPbBr 3 NCs was significantly improved by the introduction of Cs 4 PbBr 6 , one such feature being their thermal stability. [189][190][191][192] In a heating and cooling cycle, the PL intensity of pristine CsPbBr 3 and CsPbBr 3 /Cs 4 PbBr 6 composite was quenched as the temperature increased. During the cooling procedure, the quenching was gradually recovered, but never recovers to the original state.…”
Section: Nanosized Compositementioning
confidence: 99%
“…Recently, IPeNCs have been composited with polymers to enhance their stability against moisture, light, and heat. Compared with other techniques, blending IPeNCs with a commercial polymer, such as polymethylmethacrylate, poly(laurylmethacrylate), polydimethylsiloxane, polystyrene, poly(styrene-ethylene-butylene-styrene), and thermoplastic polyurethane, is a relatively easy and effective method for protecting IPeNCs [21][22][23][24][25][26][27]. However, during the time-consuming blending process in air, IPeNCs often decompose and agglomerate owing to the large difference in the polarity between the IPeNCs and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…To further demonstrate the outstanding thermal stability of the SCP@MSNs‐PDMS film, the comparisons of the PL retention and cycle number after heating–cooling cycle of SCP@MSNs‐PDMS film with some latest reported results were shown in Figure 3j. [ 26,33–40 ] It can be observed that even being tested at the highest testing temperature and longest heating–cooling cycles, SCP@MSNs‐PDMS film represented by the asterisk presented the best room temperature PL retention compared with the results reported in the literature, which further proved the ultra‐excellent thermal stability of SCP@MSNs‐PDMS film.…”
Section: Resultsmentioning
confidence: 57%
“…To further demonstrate the outstanding thermal stability of the SCP@MSNs-PDMS film, the comparisons of the PL retention and cycle number after heating-cooling cycle of SCP@MSNs-PDMS film with some latest reported results were shown in Figure 3j. [26,[33][34][35][36][37][38][39][40] It can be observed that even being tested at the highest testing temperature and longest heating-cooling cycles, SCP@MSNs-PDMS film represented by the asterisk presented Small 2022, 18, 2107452 The emission wavelengths of g) CsPbBr 3 QDs, h) SCP-PDMS film, and i) SCP@MSNs-PDMS film after heating-cooling cycle tests at different temperatures (60, 100, 150, 200 °C). j) The comparisons of the PL retention and cycle number after heating-cooling cycle of our results with some latest reported results.…”
Section: Resultsmentioning
confidence: 99%